Development of Representative Envelope Types in Existing Public Building for Green Remodeling - Oh, Ji Hyun; Kim, Hye Gi; Kim, Sun Sook (Journal of the Architectural Institute of Korea, 2021)
In Korea, public buildings are leading the green remodeling business as one of the carbon neutral strategies. Retrofitting envelope of existing buildings is considered essential for green remodeling because it affect appearance, energy use of buildings and, also occupant’s comfort. In view of constructability and cost, prefabricated envelope system have an advantage and could contribute to the activation of green remodeling business. Therefore, as the previous research for developing prefabricated envelope system, this paper aims to analyze the characteristics of existing public office buildings envelope in Korea. The survey was conducted by using web portal site “road view” function after appropriate sample design. Based on the survey, the envelope characteristics were categorized into 9 items which the orientation of main entrance, shape of plan, elevation composition, shape of openings, shape of constructions, window to wall ratio, envelope construction method, window projection and window type. We will use this results for deriving representative envelope types of public building and prefabricated envelope module design.
Keywords: Energy Efficiency; Envelope Design; Existing Building; Green Remodeling; Public Building; Representative type